2015
DOI: 10.5367/te.2014.0386
|View full text |Cite
|
Sign up to set email alerts
|

Why Negative Outputs are Often Ignored: A Comprehensive Measure of Hotel Performance

Abstract: Studies often overlook negative outputs when measuring hotel performance. This paper investigates the consequences of such omissions by comparing two performance models, one that includes negative outputs (customer complaints) and one that excludes negative outputs. The authors show that excluding negative outputs underestimates the efficiency and productivity results. The results also indicate important differences in the performance ranking of hotels when negative outputs were excluded from the model. The au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…Foreign trade dependent degree (FTDD) is measured by the ratio of trade (regional imports plus exports) to regional GDP. In line with previous studies (Huang et al, 2012), the destination's openness and connectivity also affect hotel performance (Assaf and Cvelbar, 2015).…”
Section: Control Variables In Eq (5)supporting
confidence: 89%
See 3 more Smart Citations
“…Foreign trade dependent degree (FTDD) is measured by the ratio of trade (regional imports plus exports) to regional GDP. In line with previous studies (Huang et al, 2012), the destination's openness and connectivity also affect hotel performance (Assaf and Cvelbar, 2015).…”
Section: Control Variables In Eq (5)supporting
confidence: 89%
“…The hotel industry in a province with higher transportation accessibility (TA) seems more likely to be technically efficient. The finding of a positive influence of transportation accessibility is consistent with Assaf and Cvelbar (2015), who found that the quality of the transport infrastructure has a significant positive impact on hotel performance. Hu et al (2010) found similar evidence in the case of Taiwan.…”
Section: Influences Of External Factors On Hotel Industry Efficiencysupporting
confidence: 87%
See 2 more Smart Citations
“…Several noteworthy implications emerge from the analysis on the effects of the contingent variables. First, hotel size has a significant negative influence on hotel performance (Assaf and Cvelbar, 2015). This result is unexpected because it shows that small hotels exhibit superior performance in the context of Rimini.…”
Section: Discussionmentioning
confidence: 99%